The Issa Valley in Censorship Documents. On the Thaw Reception of Czesław Miłosz’s Novel - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Czesław Miłosz’s The Issa Valley [Dolina Issy] was published in the Paris Literary Institute in 1955 and soon after started paving its way to readers in the author’s native country, in spite of the censorship. This article traces back the novel’s reception in the so-called Thaw (post-Stalin) period (1955–1957) in the light of official domestic publications and the documents of the Censorship Office. Those years saw publication of several argumentative and favourable essays on the novel (by e.g. I. Sławińska, J. Błoński, J. Zawieyski). The censors banned just one extensive discussion text on The Issa Valley, by Jarosław-Marek Rymkiewicz, and this owing to where it was published. A ban on publishing the poet’s works in a nonserial form was maintained. In that transitional period, new directives were coming from the communist-party headquarters, and the censors would often consult the heads of departments they reported to, or the Central Censorship Office directly. The situation grew severer by 1958, with the poet’s name being consistently removed from most publications.